The “arrhythmic” presentation of peripartum cardiomyopathy: case series and critical review of the literature - Peretto, Giovanni; Micaglio, Emanuele; Ciconte, Giuseppe; Maia, Marianna; Luzzi, Martina; Cariello, Marianna; Bonfanti, Adele Gabriella Rosa; Lazzeroni, Davide; Anastasia, Luigi; Cavoretto, Paolo; Chieffo, Alaide; Della Bella, Paolo; et al. (Frontiers in Cardiovascular Medicine, 2024)
Peripartum Cardiomyopathy (PPCM) is a polymorphic myocardial disease occurring late during pregnancy or early after delivery. While reduced systolic function and heart failure (HF) symptoms have been widely described, there is still a lack of reports about the arrhythmic manifestations of the disease. Most importantly, a broad range of unidentified pre-existing conditions, which may be missed by general practitioners and gynecologists, must be considered in differential diagnosis. The issue is relevant since some arrhythmias are associated to sudden cardiac death occurring in young patients, and the overall risk does not cease during the early postpartum period. This is why multimodality diagnostic workup and multidisciplinary management are highly suggested for these patients. We reported a series of 16 patients diagnosed with PPCM following arrhythmic clinical presentation. Both inpatients and outpatients were identified retrospectively. We performed several tests to identify the arrhythmic phenomena, inflammation and fibrosis presence. Cardiomyopathies phenotypes were reclassified in compliance with the updated ESC guidelines recommendations. Arrhythmias were documented in all the patients during the first cardiological assessment. PVC were the most common recorder arrhythmias, followed by VF, NSVT, AF, CSD.